Economics of the environment : selected readings (New York : W. W. Norton, 2000)
Overview and principles. The costs of environmental protection. The benefits of environmental protection. The goals of environmental policy...
Keywords: Environmental policy; Economic aspects; Pollution; Pollution -- Economic aspects; Environmental policy -- Costs